How The Burger War Was Won: An Analysis Of 18 Years of Data on Customer Hamburger Preferences - Divine, Richard; Taelman, James Arthur (Integrasi Sains Media, 2025)
Survey data collected over 18 years via a repeated cross-sectional design was examined to explore customer preference between the two main competitors in the fast-food hamburger industry: McDonald's and Wendy’s. The primary purpose of the study is to determine whether burger preference has changed over the time series and the relative importance of price and taste in determining restaurant preference. Results of the study show no significant time series effect for preference but a trend toward McDonald's in terms of intentions to visit. McDonald’s is slightly preferred over Wendy’s overall, and taste is an overwhelmingly more important consideration than the price in determining preference, even though the results show respondents consider Wendy’s to be the better-tasting competitor.